Development of Texture and Shelf Life Time Model of Sapote Fruit (Achras sapota L.) with Temperature and Pressure Variation under Hypobaric Storage - Hawa, La Choviya (Jurnal Teknologi Pertanian, 2006)
The objective of this research was to develop a model of texture and shelf life time of Sapote Fruit (Achras sapota L.) stored under hypobaric condition. The fruit was stored for 10 days at a various levels of combination of temperature and pressure. The temperature levels applied were 10° C and 20° C, and under a pressure of 30, 50 and 70 kPa. It was observed that the fruit stored at 10° C under the pressure level of 30 kPa had the lowest texture (186.62 g/mm/s). The model of sapote fruit texture (Ti) and shelf life time (), applicable to the above pre-determined condition, may be expressed respectively, as follows: ﻿﻿﻿..... ﻿﻿﻿﻿﻿﻿﻿﻿(please take a look the formula in pdf files) Key words: hypobaric, texture, shelf life time, sapote fruit